A coupled critical plane-area methodology to estimate fatigue life for an AISI 1045 steel with small artificial defects. (October 2022) - Queiroz, H.S.; Araújo, J.A.; Silva, C.R.M.; Ferreira, J.L.A.
Highlights: Fatigue data under push–pull, pure torsion and combined in-phase axial–torsional loadings for AISI 1045 smooth and microdefect specimens were generated; Approximate fatigue empirical curves were proposed to estimate fatigue life in defective materials; Critical plane models were strategically calibrated to estimate multiaxial fatigue life in materials with small defects. Multiaxial fatigue life was estimated by applying a new methodology for calibrating the SWT, FS and MWCM models. Abstract: The presence of notches, tears, holes, cavities, inclusions, and scratches is common in structural designs and mechanical components, that in the presence of cyclic loading can influence their resistance and fatigue life. The objective of this research is to propose and validate an approach for fatigue life estimation for materials with small defects subjected to combined loading. The approach of the project is formulated based on a calibration strategy for Fatemi-Socie, Smith-Watson-Topper and Susmel and Lazarin critical plane models, using Murakami criteria and notch factor to compute the defect effect. The results predicted by the model were compared and validated with experimental data, showing it to be a promising strategy. For further extension and a more generalized application of the proposed model, it is necessary to perform life prediction comparisons for different materials, loadings, and defect geometries.